Tipos de orquidáceas brenesianas, descritas por R. Schlechter, en el Herbario Nacional de Costa Rica - Lobo, Silvia (2016)
This note informs about the presence of seven Brenesian orchid types, described by R. Schlechter, in the Herbario Nacional de Costa Rica (CR) type collection, whose existence was unknown.